Passion Or Pressure? A Closer Look At How Gen Z Relates To Their Work - Soerjoatmodjo, Gita Widya Laksmini (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Gen Z is widely portrayed as a generation that seeks meaning and personal fulfillment in their work. But does this truly stem from genuine passion—or from internal and social pressures? This study investigates Gen Z’s work motivation by comparing two forms of work passion: harmonious and obsessive. Using data from 422 Gen Z employees across Indonesia, collected via online surveys, a paired sample t-test revealed that respondents reported significantly higher levels of harmonious passion (M = 26.22, SD = 4.80) compared to obsessive passion (M = 21.45, SD = 5.14), t(421) = 22.77, p < .001, with a large effect size (d = 1.11). These findings suggest that Gen Z is more likely to pursue work as a self-directed, meaningful endeavor rather than one driven by pressure or identity attachment. The study offers a timely reflection for Gen Z on the nature of their work engagement and provides organizations with practical insights on how to attract and retain passionate young talent. This research contributes to the broader discourse on generational work values and highlights the importance of fostering authentic motivation in the emerging workforce.